2019
DOI: 10.1111/jsr.12783
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional and longitudinal associations between psychosocial well‐being and sleep in European children and adolescents

Abstract: Research on associations of positive mental health, in contrast to mental ill‐health, with sleep duration and sleep disturbances in young populations is scarce. In particular, longitudinal studies focussing on the influence of positive mental health on sleep characteristics are lacking. Therefore, we investigated cross‐sectional and longitudinal associations of psychosocial well‐being with sleep duration and sleep disturbances. For the cross‐sectional analysis, we used data of 3‐15‐year‐old children and adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
2
19
0
1
Order By: Relevance
“…Socio-demographic variables (baseline age, sex, country, highest educational level of parents), pubertal status at follow-up and follow-up time were included as covariates in all regressions of the path model. Furthermore, psychosocial well-being was included as a covariate because of its association with sleep duration [40] and the potential role of psychosocial stressors in the development of abdominal obesity and insulin resistance [41,42]. Lastly, models were also adjusted for napping time because napping has been found to be associated with shorter nocturnal sleep duration [43].…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic variables (baseline age, sex, country, highest educational level of parents), pubertal status at follow-up and follow-up time were included as covariates in all regressions of the path model. Furthermore, psychosocial well-being was included as a covariate because of its association with sleep duration [40] and the potential role of psychosocial stressors in the development of abdominal obesity and insulin resistance [41,42]. Lastly, models were also adjusted for napping time because napping has been found to be associated with shorter nocturnal sleep duration [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, a fair agreement has been found in earlier studies between self‐reported and objectively measured sleep duration (actigraphic observations) (Lauderdale, Knutson, Yan, Liu, & Rathouz, ). Accordingly, although self‐reported data are not as precise as actigraphy, they are often used in children, due to their ease of use and minimal time and costs involved in data collection (Matricciani, ; Thumann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, on a subsample of subjects, sleep quality was investigated by asking whether the child/adolescent ‘snored’ (less than once a week/more than once a week; n = 76), had ‘trouble getting up in the morning’ (yes/no; n = 91), had ‘difficulties falling asleep’ (yes/no; n = 91), and what in general was their perceived sleep quality (very good, fairly good, fairly bad, very bad; n = 91) (Magee, Robinson, & Keane, ; Thumann et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Even if the major risk factors for hypertension, including obesity, ethnicity, family history of hypertension, dietary, and lifestyle habits are well established, sleep is an unusual and often overlooked factor. Sleep plays an essential role in the daily life of adults and in the growth of children and adolescents; an adequate amount of sleep is fundamental for human functioning and well‐being throughout the lifetime …”
Section: Introductionmentioning
confidence: 99%